$\mathbb {\mathcal {C}}^{0}$-rigidity of Lagrangian submanifolds and punctured holomorphic disks in the cotangent bundle. (3rd November 2021) - Membrez, Cedric; Opshtein, Emmanuel
Abstract: Our main result is the $\mathbb {\mathcal {C}}^{0}$ -rigidity of the area spectrum and the Maslov class of Lagrangian submanifolds. This relies on the existence of punctured pseudoholomorphic disks in cotangent bundles with boundary on the zero section, whose boundaries represent any integral homology class. We discuss further applications of these punctured disks in symplectic geometry.